Botulinum Toxin A Delivery via MMP Technique: An Emerging Therapeutic Approach for Frontal Fibrosing Alopecia - Neri, Simone Ramos Nogueira Guerra; Domingos, Marta de Oliveira; Michalany, Nílceo Schwery; Michalany, Alexandre Ozores; Kalil, Celia Luiza Petersen Vitello (Brazilian Journal of Case Reports, 2023)
Frontal Fibrosing Alopecia (FFA) is a disease of unknown etiology and pathogenesis whose prevalence has been increasing since its first description in 1994. With no cure, treatments only control the inflammatory process and disease progression, but do not reverse the changes induced by it. We report the case of a patient with early-stage FFA who underwent three monthly sessions of 30 units of Botulinum Toxin Type A administered by MMP® (Microinfusion of drugs through the skin) technique. The results showed a substantial improvement in the patient's clinical condition with inhibition of the inflammatory process and an evident increase in follicular density in the treated area.